2007
DOI: 10.1103/physreve.75.041915
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-trapping model of receptor trafficking in dendrites

Abstract: We present a model for the diffusive trafficking of protein receptors along the surface of a neuron's dendrite. Distributed along the dendrite are spatially localized trapping regions that represent submicrometer mushroom-like protrusions known as dendritic spines. Within these trapping regions receptors can be internalized via endocytosis and either reinserted into the surface via exocytosis or degraded. We calculate the steady-state distribution of receptors along the dendrite assuming a constant flux of rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 28 publications
1
45
0
1
Order By: Relevance
“…Let p(x, t) denote the probability density (per unit area) that a surface receptor is located within the dendritic membrane at position x at time t. Similarly, let R j (t), S j (t) denote the probability that the receptor is trapped at the surface of the jth spine or within an associated intracellular pool, respectively. A simple version of the 1D diffusion-trapping model of AMPA receptor trafficking takes the form (Bressloff and Earnshaw, 2007;Earnshaw and Bressloff, 2008) …”
Section: Diffusion Along Spiny Dendritesmentioning
confidence: 99%
See 1 more Smart Citation
“…Let p(x, t) denote the probability density (per unit area) that a surface receptor is located within the dendritic membrane at position x at time t. Similarly, let R j (t), S j (t) denote the probability that the receptor is trapped at the surface of the jth spine or within an associated intracellular pool, respectively. A simple version of the 1D diffusion-trapping model of AMPA receptor trafficking takes the form (Bressloff and Earnshaw, 2007;Earnshaw and Bressloff, 2008) …”
Section: Diffusion Along Spiny Dendritesmentioning
confidence: 99%
“…However, it is still unclear to what extent intracellular diffusion is anomalous in the long-time limit rather than just at intermediate times. This motivates studying diffusion in the presence of obstacles and transient traps whereby normal diffusion is recovered asymptotically (Bressloff and Earnshaw, 2007;Santamaria et al, 2006;Saxton, 1994Saxton, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that the radius of the spine neck is typically at the submicron level, which is much smaller than any other length scale of the system, we can take into account the discreteness of spines by representing the spine density as a sum of Dirac delta functions Bressloff and Earnshaw 2007;Meunier and d'Incamps 2008;Bressloff 2009):…”
Section: Pulsating Waves In the Presence Of Discretely Distributed Spmentioning
confidence: 99%
“…This Markovian model corresponds to the phenomenological approach for spine-dendrite interaction [12]. Consider now the non-Markovian case when both waiting time PDFs c i are gamma distributions c i ðtÞ ¼ [14], i.e., hx 2 ðtÞi $ t , where 0 < < 1.…”
Section: Prl 101 218102 (2008) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…In recent years, the development of confocal microscopies and other techniques allow one to study the transport and biochemical reactions on the microscopic level of a single spine and a parent dendrite [7][8][9]. There are several models for the particle transport and chemical reactions inside biological microdomains [10][11][12][13]. Santamaria et al [14] found recently that the transport of biologically inert particles (fluorescein dextran) in spiny dendrites is very slow in comparison to the standard diffusion.…”
mentioning
confidence: 99%